Optimalisasi Variasi Volume Resin Komposit Serat Limbah Karung Glangsing - Utsman Syah Amrullah; Riyanto Heri Nugroho (Polinema Press, Politeknik Negeri Malang, 2018)
The waste of sacks glangsing of rice, fertilizer, sugar, animal feed and others can cause serious problems, example in the household scale causes the storage process in the warehouse very difficult because takes place, also invites mices to come. And on a larger scale the excessive use of sacks of glangsing causes waste and pollution to the soil due to the difficult and time-consuming decomposition. Efforts to utilize waste sacks glangsing are make it as a reinforcing fiber composite material. It is expected to be an alternative fiber replacement fiber material available on the market. The stiffness or flekstural test is taken to show comparison the composite. The composite material (with glass fiber reinforce) which made in equal thickness and simultaneously, showed that the resin volume of 15 cc applied to fiberglass fiber with an area of ​​180 x 180 mm, with 3 layers have a deflection 1.2 mm at 31.5 grams load. While the volume of 30 cc resin gives a deflection 0.25 mm at the same load. While specimens that use glangsing sack fiber did not provide a good enough stiffness. At 31.5 gram load the deflections are very large 12 mm for 15 cc resin volume, and 9.8 mm for 25 cc resin volume, and 4.5 mm for resin volume of 30 cc, and 4.5 mm for resin volume 45 cc. Beside a large deflection, the composite with sack glangsing fibers is apparently subjected to delamination (exfoliation). Therefore, the use of glangsing sack fiber is not recommended.